2015
DOI: 10.1142/s0218127415500595
|View full text |Cite
|
Sign up to set email alerts
|

On the Limit Cycles for a Class of Continuous Piecewise Linear Differential Systems with Three Zones

Abstract: In this paper we consider a class of planar continuous piecewise linear vector fields with three zones. Using the Poincaré map we show that these systems admit always a unique limit cycle, which is hyperbolic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In fact, as far as we know, the studies found in the pertinent literature deal with piecewise smooth systems with three zones in the plane with at least one equilibrium point which can be real or virtual. This is the case, for instance, in the studies carried out in [3], [6], [7], [8], [9], [10]. We emphasize that in these articles the authors studied the existence and the number of limit cycles under the hypothesis of the continuity of the vector fields in the separation curves which are straight lines.…”
mentioning
confidence: 94%
“…In fact, as far as we know, the studies found in the pertinent literature deal with piecewise smooth systems with three zones in the plane with at least one equilibrium point which can be real or virtual. This is the case, for instance, in the studies carried out in [3], [6], [7], [8], [9], [10]. We emphasize that in these articles the authors studied the existence and the number of limit cycles under the hypothesis of the continuity of the vector fields in the separation curves which are straight lines.…”
mentioning
confidence: 94%